(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
AR has become a revolutionary device in the educational environment, providing engagements of learning with a sense of being in another world and applying these concepts in reality. This paper will discuss the effectiveness of AR simulations in learning sports nutrition and health decision-making in undergraduates within a sports science degree. The study by incorporating AR based situations that simulate real life dietary and health decisions by sportspeople fulfils the research gap of lack in experiential learning opportunities in the conventional sports nutrition programs. The methods used were mixed-methods and a sample of 120 participants who participated in an AR simulations over 12 weeks was used in the study involving two universities. Pre-intervention and post-intervention quantitative data showed a great improvement in the retention of knowledge (p < 0.01) and the confidence in decision-making (p < 0.05). Qualitative responses were seen under the improved involvement and perceived relatability of the simulations. The results are that AR simulation can have a significant role of complementing traditional teaching techniques but the challenges like the accessibility to technology and training of an instructor still exist. The suggestions on the implementation of AR in sports science education are given which focus on scalable implementation and design inclusivity.